Protection against brain injury after ischemic stroke by intravenous human amnion epithelial cells in combination with tissue plasminogen activator - Barreto-Arce, Liz J.; Kim, Hyun Ah; Chan, Siow Teng; Lim, Rebecca; Drummond, Grant R.; Ma, Henry; Phan, Thanh G.; Sobey, Christopher G.; Zhang, Shenpeng R. (Frontiers in Neuroscience, 2023)
Background: Thrombolytic agents such as tissue plasminogen activator (tPA) are the only drug class approved to treat ischemic stroke and are usually administered within 4.5 h. However, only 20% of ischemic stroke patients are eligible to receive the therapy. We previously demonstrated that early intravenous administration of human amnion epithelial cells (hAECs) can limit brain inflammation and infarct growth in experimental stroke. Here, we have tested whether hAECs exert cerebroprotective effects in combination with tPA in mice. Methods: Male C57Bl/6 mice were subjected to middle cerebral artery occlusion for 60 min followed by reperfusion. Immediately following reperfusion, vehicle (saline, n=18) or tPA (10 mg/kg; n=75) was administered intravenously. After 30 min of reperfusion, tPA-treated mice were injected intravenously with either hAECs (1x106; n=32) or vehicle (2% human serum albumin; n=43). A further 8 sham-operated mice were treated with tPA+vehicle. Mice were designated to be euthanised at 3, 6 or 24 h post-stroke (n= 21, 34, and 38, respectively), and brains were collected to assess infarct volume, blood-brain barrier (BBB) disruption, intracerebral bleeding and inflammatory cell content. Results: There was no mortality within 6 h of stroke onset, but a high mortality occurred in tPA+saline-treated mice between 6 h and 24 h post-stroke in comparison to mice treated with tPA+hAECs (61% vs 27%, p=04). No mortality occurred within 24 h of sham surgery in mice treated with tPA+vehicle. We focused on early infarct expansion within 6 h of stroke and found that infarction was 50% larger in tPA+saline- than in vehicle-treated mice (233 mm3 vs 152 mm3) but not in mice receiving tPA+hAECs (132 mm3, p=0.01 vs tPA+saline) in which intracerebral hAECs were detected. Similar to the profiles of infarct expansion, BBB disruption and intracerebral bleeding in tPA+saline-treated mice at 6 h was 50-60% greater than in vehicle-treated controls (2.60.5 vs 1.60.2, p=0.05) but not after tPA+hAECs treatment (1.70.2, p=0.10 vs tPA+saline). No differences in inflammatory cell content were detected between treatment groups. Conclusions: When administered following tPA in acute stroke, hAECs attenuate infarct growth in association with less BBB disruption and lower 24 h mortality.